Pencegahan dan Pengendalian Infeksi Silang pada Tindakan Ekstraksi Gigi di Poli Gigi Puskesmas Kassi - kassi Kota Makassar - Fidzah Nurfajrina Murad; Arfiah Jauharuddin; Dewi Sartika; Suciyati Sundu; Rumaisha Soumena (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2024)
Cross-infection is one of the main risks faced in medical procedures, including tooth extraction in health facilities such as the dental clinic of the Health Center. This infection can occur through direct contact with blood, saliva, or non-sterile medical equipment, as well as through transmission from patients to medical personnel or vice versa. This study aims to evaluate the effectiveness of efforts to prevent and control cross-infection in tooth extraction procedures at the Dental Clinic of the Kassi - Kassi Health Center. The methods used in this study include counseling to medical personnel regarding cross-infection prevention protocols, including hand hygiene, use of personal protective equipment (PPE), and sterilization of equipment. Evaluations were conducted before and after counseling through questionnaires filled out by the participants. The evaluation results showed a significant increase in understanding, awareness, and implementation of cross-infection prevention protocols. Before counseling, only 60% of participants had a good understanding of cross-infection, while after counseling, this figure increased to 90%. Improvements were also seen in awareness of hand hygiene, knowledge of PPE use, sterilization procedures, implementation of SOPs, and handling of high-risk patients. The conclusion of this study shows that counseling and strict implementation of protocols can significantly reduce the risk of cross-infection in tooth extraction procedures. Therefore, it is recommended that similar counseling be held routinely to ensure consistent and sustainable implementation of infection prevention in the Puskesmas environment.